Indoleamine 2, 3‐dioxygenase 2 depletion suppresses tumor growth in a mouse model of Lewis lung carcinoma. Issue 10 (25th September 2019) - Yamasuge, Wakana; Yamamoto, Yasuko; Fujigaki, Hidetsugu; Hoshi, Masato; Nakamoto, Kentaro; Kunisawa, Kazuo; Mouri, Akihiro; Nabeshima, Toshitaka; Saito, Kuniaki
Abstract: Tryptophan metabolism is important to induce immune tolerance in tumors. To date, 3 types of tryptophan‐metabolizing enzymes have been identified: indoleamine 2, 3‐dioxygenase 1 and 2 (IDO1 and IDO2) and tryptophan 2, 3‐dioxygenase 2. Numerous studies have focused on IDO1 as its expression is enhanced in various cancers. Recently, IDO2 has been identified as a tryptophan‐metabolizing enzyme that is involved in several immune functions and expressed in cancers such as pancreatic cancer. However, the biological role of IDO2 in the induction of immune tolerance in tumors has not yet been reported. In the present study, we examined the effects of Ido2 depletion on tumor growth in a mouse model of Lewis lung carcinoma by using Ido2‐knockout mice. Ido2‐knockout mice had reduced tumor volumes compared to WT mice. Furthermore, Ido2 depletion altered the tumor microenvironment, such as tryptophan accumulation and kynurenine reduction, leading to enhancement of immune cell invasion. Finally, enzyme‐linked immunospot assay revealed that Ido2 depletion enhanced γ‐interferon secretion in the tumor. In conclusion, Ido2 is an important immune regulator in the tumor microenvironment. Our data indicate that IDO2 is a potential target for cancer treatment and drug development. Abstract : Indoleamine 2, 3‐dioxygenase 2 (Ido2) deletion reduced tumor volumes in a mouse model of Lewis lung carcinoma. Furthermore, Ido2 depletion led to enhancement of immune cell invasion, and γ‐interferon secretion in the tumor. Our data indicate that Ido2 is an important immune regulator in the tumor microenvironment.